Rational Engineering of BODIPY‐Bridged Trisindole Derivatives for Solar Cell Applications. Issue 9 (7th April 2017) - Bulut, Ibrahim; Huaulmé, Quentin; Mirloup, Antoine; Chávez, Patricia; Fall, Sadiara; Hébraud, Anne; Méry, Stéphane; Heinrich, Benoît; Heiser, Thomas; Lévêque, Patrick; Leclerc, Nicolas
Abstract: Boron dipyrromethene (BODIPY) and its derivatives are known to be efficient photon‐harvesting chromophores. However, their study as active materials in bulk heterojunction (BHJ) solar cells is still scarce. In this study, the development of new synthetic ways to design original BODIPY‐based dumbbell‐shape molecules, including a first 2, 3, 5, 6‐tetravinyl aromatic BODIPY molecule, is reported. High fill factors can be obtained in BHJ solar cells when blended with a fullerene derivative, leading to a new record BODIPY‐based power conversion efficiency of 5.8 %. Abstract : Let's get ready to dumbbell ! Boron dipyrromethene‐based (BODIPY) dumbbell‐shaped molecules, including a first 2, 3, 5, 6‐tetravinyl aromatic BODIPY derivative, have been synthesized to strengthen π‐stacking abilities. Used as a p‐type material, high fill factors can be obtained in bulk heterojunction solar cells when blended with a fullerene derivative, leading to a new BODIPY‐based record power conversion efficiency of 5.8 %.